Analisis Perubahan Harga iPhone dan Gaya Hidup terhadap Keputusan Pembelian - Siti Auritsa Khoiriah; Sri Putri Rahayu; Sri Mulyeni (Jurnal Manajemen Kreatif dan Inovasi, 2026)
Business competition has become increasingly intense, requiring companies to understand consumer behavior more deeply, especially in the smartphone industry. The iPhone, as a premium product, presents a unique phenomenon in which price increases do not necessarily reduce consumer interest but instead strengthen perceptions of exclusivity and social prestige. This study aims to analyze the influence of price changes and lifestyle on iPhone purchase decisions. The research method applied is a literature study with a qualitative approach, by collecting and analyzing relevant journals and scientific articles related to consumer behavior, price, and lifestyle. The findings reveal that most studies confirm that both price and lifestyle have a positive and significant effect on iPhone purchase decisions, although some variations exist where either price or lifestyle shows no significant impact. Consumers are found to consider not only the functional aspects of the product but also its symbolic and social values. High prices are often perceived as indicators of quality and prestige, while modern lifestyles and social media trends position the iPhone as a status symbol and part of self-identity, particularly among younger generations. In conclusion, iPhone purchase decisions are not solely driven by economic factors but are also influenced by psychological and social dimensions. Therefore, producers must maintain product quality and strong brand image while adapting marketing strategies to evolving consumer lifestyles.